URGENSI PENDIDIKAN WIRAUSAHA (Studi Pada Pelaku usaha di desa Batu Merah Kota Ambon) - M Sahrawi Saimima; Andi Ismai Marasabessy (IAIN Ambon, 2022)
Abstract This research was conducted due to the phenomenon of the development of business actors during the Covid-19 pandemic in the city of Ambon. The object of research in this study was business actors in the red stone village of Ambon city. This research uses a qualitative research approach. The results showed that many business actors are those who do not have a special educational background in entrepreneurship. The results of field observations show that business actors started businesses due to the large amount of government assistance and the large return of students from outside the city to the city of Ambon and provided development to business actors in the city of Ambon. The results of the study provide information on the importance of knowledge to business actors in the red stone village of Ambon city about entrepreneurship so that their business can continue to grow in any condition.Keywords : Covid-19, Businessman, Entrepreneur Education